Identifying and prioritizing factors of the formation of investment strategy in the Ghana's downstream oil and gas industry - Michael Karikari Appiah; Bayu Taufiq Possumah; Nur Azura Sanusi (Cogent Business & Management, 2021)
We present a new model to identify and prioritize factors affecting small and medium enterprises (SMEs) investment intentions by integrating existing models. Structured questionnaire is used to sample respondents from the Ghanaian SMEs between 2017 and 2018. Data analyses have been conducted using variance-based Smart Partial Least Square (SmartPLS) technique. The major findings of the study are that macro environment factors, resource competitive strategies and oil and gas policy-specific factors are the significant determinants of SMEs investment intentions. Again, the study revealed that the resource competitive strategies significantly mediate the relationship between macro environment factors, industry force, oil and gas policy support and investment intentions. These results are robust and consistent with resource-based view, theory of constraint and theory of strategic positioning. Moreover, these results contribute new knowledge towards developing investment strategy for the downstream oil and gas industry. Besides, these findings have managerial implications needed by policy makers to renew commitment and provide the needed framework to investors to enhance indigenous participation in the industry.
Keywords: D02; O17; P31; 650; Integrated model; RBV; theory of constrain; theory of strategic positioning; Ghana